Building city branding of Yogyakarta as a cultural city: A youtube user-generated content analysis - Siswantoro Siswantoro; Ihsanul Ikhwan (Indonesian Tourism Journal, 2024)
This study aims to analyze the role of social media in the form of Youtube in promoting the city branding of Yogyakarta, which has been known as a city of culture. Specifically, this research develops three research questions: 1) “What is the role of Youtube social media in promoting city branding of Yogyakarta?”, 2) “Does the cultural aspect appear as the main image of Yogyakarta on Youtube social media?”, 3) “What are the roles of individuals and institutions in the process of Yogyakarta city branding as a cultural city on social media Youtube?”. A total of 240 user-generated content on Youtube were collected via #yogyakarta over a period of 1 month. The content is then analyzed using content information analysis. This study adopts 12 different categories in order to analyze video content. Related to the research question, the research results show that social media plays an important role in creating city branding in Yogyakarta. In this case, users are able to describe Yogyakarta from various perspectives through social media (Youtube). Second, the cultural aspects identified are not the main aspects related to Yogyakarta, but local culinary delights and historical buildings. Nonetheless, these two aspects have a long history and connection with the culture in Yogyakarta. For the last question, the research results show that individuals play a bigger role in building Yogyakarta city branding than institutions. This shows that individuals are positioned not only as consumers of social media but also as producers of social media.